A Study on the waterproof properties of coarse wool - Du , Hyan Yan; Gombojav, Ganbat; Baatar, Narantya (Mongolian Journal of Agricultural Sciences, 2022)
The characteristics of the capillary fibers in the composition of sheep's wool were compared with the histological structure of the capillaries of other animals. The scale height of sheep coarse wool capillary varies from 9.12 to 24.4 μm, with an average of 15.03 μm, which is 2.54 to 4.96 μm longer than the scale height of yak and camel hair, and 3.14 μm shorter than goat hair. When determining the wetting state of the surface of the capillary fibers by measuring the contact angle of the water to the fibers, we found that the fibers exhibited a relatively low water-absorption ability of 112.10 (units??) . Based on the unique water repellency properties of these fibers, we can optimize waterproof non-woven textile technology. Хонины ноосны хялгасан ширхэгтийн ус нэвтрэх шинж чанарыг тодорхойлсон дүн Хонины ноосны бүрэлдэхүүн дэх хялгасан ширхэгтийн шинж чанарыг бусад малын хялгасны гистологи бүтэцтэй харьцуулан судалсан. Хонины бүдүүн ноосны хялгасан ширхэгтийн хайрсны өндөр 9.12-24.4мкм хооронд хэлбэлзэж дунджаар 15.03 мкм, сарлаг, тэмээний хялгасны хайрсны өндрөөс 2.54-4.96 мкм-оор урт, ямааны хялгаснаас 3.14 мкм-оор богино байна. Хялгасан ширхэгтийн гадаргуун норголтын байдлыг шүргэлтийн өнцгийг тодорхойлоход 112.10 байгаа нь гидрофоб шинж чанартай норголтын зэргээр маш бага норох ангилалд багтдаг, ус үл шингээх чадвартай болохыг тогтоов. Хялгасан ширхэгтийн ус түлхэх өвөрмөц шинж чанарт тулгуурлан ус үл нэвтрэх нэхээсгүй нэхмэл эдлэл үйлдвэрлэх технологийг оновчлон гаргалаа. ТҮЛХҮҮР ҮГ: ус үл нэвтрэх, хялгас, ноолуур, хайрсны хэлбэр, гистологи бүтэц